Time-resolved Optical Properties of SiNW Oriented in <211> Crystallographic Direction. (2019) - Fatima,; Forde, Aaron; Inerbaev, Talgat M.; Oncel, Nuri; Kilin, Dmitri S.
ABSTRACT: Silicon nanowires (SiNWs) show unique optoelectronic properties such as band gap, radiative and nonradiative relaxations. In this research, the optoelectronic properties of <211> SiNW are calculated by combining time-dependent density matrix methodology. Description of photo-excited dynamics processes is enabled by computing "on–the–fly" nonadiabatic couplings (NAC) between electronic and nuclear degrees of freedom using density functional theory (DFT). The dynamics of electronic degrees of freedom is propagated by the reduced density matrix with Redfield equation of motion. Oscillator strengths are used to compute radiative relaxation and to generate time resolved photoluminescence (PL) spectrum. Analysis of the simulated nonradiative decay shows that high-energy photoexcitation relaxes to the band gap edge on the order of 1 ps. We also simulate time-resolved emission spectra of the <211> SiNW that reveals optical emissions above the optical band gap. These emission features are attributed to the interband transitions. The results of this study can be useful for the material choice for optoelectronic applications.